2008
DOI: 10.1155/2008/942758
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy: A powerful technique for biochemical analysis and diagnosis

Abstract: The present work focuses on the recent applications of Raman spectroscopy (RS) on biochemical analysis and diagnosis of several biological materials with or without pathological alterations. Important published works about Raman spectroscopy and its use for medical applications were critically reviewed, including articles form our group in order to evaluate the state of the art of the subject. The potential for sample characterization with RS associated to the possibility of analysisin situmakes this instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 110 publications
(139 reference statements)
0
39
0
5
Order By: Relevance
“…Conversely, apart from the advantage of being able to use FT techniques with 1064-nm excitation, the lack of fluorescence, which often accompanies visible irradiation with biological samples and swamps the Raman spectrum, is an additional advantage. These advantages combined often outweigh the disadvantages and have resulted in the extensive use of FT-Raman studies on biological samples (Gierlinger and Schwanninger 2007;Moreira et al 2008;Movasaghi et al 2007;Parker 1994).…”
Section: Raman Spectroscopic Microprobesmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, apart from the advantage of being able to use FT techniques with 1064-nm excitation, the lack of fluorescence, which often accompanies visible irradiation with biological samples and swamps the Raman spectrum, is an additional advantage. These advantages combined often outweigh the disadvantages and have resulted in the extensive use of FT-Raman studies on biological samples (Gierlinger and Schwanninger 2007;Moreira et al 2008;Movasaghi et al 2007;Parker 1994).…”
Section: Raman Spectroscopic Microprobesmentioning
confidence: 99%
“…Because of the rapid expansion of biological applications of vibrational spectroscopic mapping and imaging techniques, it is not possible to provide an extensive review of recent research within the space limitations of this article, but an overview of the diversity of applications in medicine and biology, including medical diagnostics, studies of physiological and diseases processes and treatments of diseases and plant biology, can be found in a number of recent reviews (Bailo and Deckert 2008;Bhargava 2007;Boskey and Mendelsohn 2005;Chan et al 2008;Gierlinger and Schwanninger 2007;Levin and Bhargava 2005;Moreira et al 2008;Movasaghi et al 2007;Petibois and Guidi 2008;Petter et al 2009;Srinivasan and Bhargava 2007;Swain and Stevens 2007). As outlined in these reviews and the current review, the increase in the speed of acquisition, sensitivity, discrimination and spatial resolution of the emerging techniques of vibrational spectroscopic microscopies has greatly expanded the horizons of what is possible in terms of an explosion of new knowledge that is being generated.…”
Section: Applications To Biological Systemsmentioning
confidence: 99%
“…It is interesting to register that in a previous article, our group divulgated a new optical fiber catheter with distal end bending mechanism control [14] that together with the present data will permit a total control of the movements of the catheters in organs and tissues of difficult accessibility, favoring a improvement in the analysis by Raman spectroscopy. In fact, we have applied instrumental tools, such as Raman spectroscopy, in order to improve the methodologies employed in biomedical engineering, allowing, in this way, a significant advancement in the clinical procedures of diagnosis [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed the accuracy of the diagnostic technique based on Raman spectroscopy in various biological tissues such as the cervical lesions [1,22], gastric tissues [15,30], colon [20], thyroid [18], larynx [34], skin [2,17], bladder [6,10], among others. In prostate tissues, several studies indicated the diagnostic capability of various optical techniques [5,7,9,33].…”
Section: Introductionmentioning
confidence: 91%
“…The Raman technique evaluates the interaction of the incident monochromatic light with the molecules. This interaction causes a loss or a gain in the vibrational energy of molecules, which appears as bands at specific positions of the molecular group vibrations [22]. A Raman spectrum gives insight into the molecular composition of the sample and could provide diagnostic information for the pathology under study.…”
Section: Introductionmentioning
confidence: 99%